2023
DOI: 10.31055/1851.2372.v58.n3.38251
|View full text |Cite
|
Sign up to set email alerts
|

Floral nectary structure, nectar presentation and morpho-anatomical analysis of male‐fertile and male‐sterile anthers in onion (Allium cepa, Amaryllidaceae)

Abstract: Background and aims: The onion (Allium cepa var. cepa) is an allogamous species in which male-sterile lines have been developed. However, the structure of the flower and floral nectaries have only been briefly described. The objective of this study is to update the floral anatomy data, comparing the gynoecium and androecium of male-fertile and male-sterile lines, and to analyze the three-dimensional structure of the floral nectary. M&M: Conventional optical and scanning electron microscopy techniques were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…An anatomical study of the onion flower showed that there are no differences between fertile and male‐sterile lines involving the floral structure in general or the gynoecium or nectary structure in particular. The fundamental difference between fertile and male sterile lines (MSL) is the interruption of male gametogenesis and the process of anther dehiscence (Gonzalez et al., 2023). Onion flowers exhibit heterostyly, characterized by differences in floral traits, such as length of style, tepals, and anthers between flowers on an individual plant or between cultivars (Soto et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An anatomical study of the onion flower showed that there are no differences between fertile and male‐sterile lines involving the floral structure in general or the gynoecium or nectary structure in particular. The fundamental difference between fertile and male sterile lines (MSL) is the interruption of male gametogenesis and the process of anther dehiscence (Gonzalez et al., 2023). Onion flowers exhibit heterostyly, characterized by differences in floral traits, such as length of style, tepals, and anthers between flowers on an individual plant or between cultivars (Soto et al., 2013).…”
Section: Introductionmentioning
confidence: 99%